2022
DOI: 10.1029/2021rs007412
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Common Reflecting and Absorbing Building Materials on THz Multipath Channels

Abstract: THz band communication has the potential to meet the high data rate demands of many current and future applications. However, before these networks are realized, extensive channel measurements are needed in order to characterize the wireless channel at these frequencies, in order to inform system design and deployment. In the current paper, we present a set of double‐directional channel measurements that are conducted in several relevant indoor and outdoor scenarios. Our aim is to see the effect of common buil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In the D2D measurements only the horizontal plane was scanned, while in the microcellular measurements, azimuthal scans were performed for multiple elevation cuts. The same setup was also used for indoor measurements, see [46].…”
Section: B Outdoor Environmentsmentioning
confidence: 99%
“…In the D2D measurements only the horizontal plane was scanned, while in the microcellular measurements, azimuthal scans were performed for multiple elevation cuts. The same setup was also used for indoor measurements, see [46].…”
Section: B Outdoor Environmentsmentioning
confidence: 99%
“…It may be premature to develop a geometry-based model for the sub-THz band, because of lack of sufficient knowledge about wave-interacting objects that produce MPCs to the radio link; it is still an open question, e.g., i) what is a typical material of objects that cause meaningful power contributing to the link, ii) what is a typical size of meaningful objects and finally, iii) how much contribution do various objects make in generating multipath clusters. While the number of MPCs and beams has been discussed at above-100 GHz band, e.g., [5], [14], [15], their understanding of the physical environment is not available. These open questions must be addressed through experiment-based studies of wave propagation.…”
Section: Introductionmentioning
confidence: 99%
“…These open questions must be addressed through experiment-based studies of wave propagation. As a basic work, several studies reported isolated measurements of waveobject interaction to reveal, e.g., reflection and penetration losses at sub-THz frequencies [3]- [5], [7], [16]- [18]. More sophisticated studies as summarized in Table I identify waveinteracting objects in multipath channels in lower frequency bands [19]- [24], forming a basis for development of geometrybased channel models [12], [19], [25]- [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation